FP-LAPW calculations of the EFG at Cd Impurities in rutile SnO2 - Errico, Leonardo Antonio (2001)
We report an ab initio study of the electric-field gradient (EFG) at Cd impurities located at the cation site in the semiconductor SnO2 (rutile phase). The study was performed with the WIEN97 implementation of the FP-LAPW method. In order to simulate the diluted Cd-impurity in the SnO2 host and to calculate the electronic structure of the system we used a 72-atoms super-cell, studying the relaxation introduced by the impurity in the lattice. The free-relaxation process performed shows that the relaxations of the oxygen nearest-neighbors of the impurity are not isotropic. Our prediction for the EFG tensor are compared with experimental results and point-charge model predictions. Vol: 136/137